SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN LOKASI PEMBUKAAN CABANG USAHA ONLINE BICYCLE INDONESIA DENGAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) DAN TECHNIQUE FOR ORDER PREFERENCE BY SIMILARITY TO IDEAL SOLUTION (TOPSIS) - Adha, Rizki; Tjahjanto, Tjahjanto (Fakultas Teknik Universitas Muria Kudus, 2020)
The choice of business location will affect the risks and benefits of the company as a whole. This condition occurs because the location greatly affects the fixed costs and variable costs, both in the medium term and long term. The location of the business should be taken into account at the time of planning, so that the business to be run can be organized implementation in the future. Online Bicycle Indonesia is a startup engaged in goods and food delivery services by using online-based bike, will open branches in several cities and districts in Tangerang Raya area so that the result of choosing the right branch location, required a dynamic decision support system that can later be used as consideration of managers in the process of selecting branch locations. Problems in selecting branch of this company can be used Decision Support System using AHP-TOPSIS method. Analytical Hierarchy Process (AHP) method has advantages based on pair comparison matrix and perform consistency analysis, while Technique For Order Preference by Similarity to Ideal Solution (TOPSIS) method can solve practical decision making, because the concept is simple and easy to understand, and have the ability to measure the relative performance of decision alternatives. The results of the study show Kota Tangerang Selatan is superior to the weight of 0.824, the two Kota Tangerang with a weight of 0.732 and three Kabupaten Tangerang with a weight of 0.0, The decision taken can be accounted for by the calculation of AHP-TOPSIS as a model in the decision support system